PROCESSED TILAPIA FISH IN SIANTAR SELATAN DISTRICT, SIMALUNGUN REGENCY - Riada Mareny; Jumadiah Wardati; Eka Sihombing (Universitas Efarina, 2022)
South Siantar District, Simalungun Regency is an area around which there are many home industries, for example, craftsmen processing mussels and mussel paste, slaps, ovens, tins, snacks, prawn crackers, fish crackers, mussel crackers and others. Sumorame is one of the Ajibata Villages in the Toba District consisting of several neighborhoods, where each neighborhood has community empowerment activities which are mostly managed by PKK women. Such activities include gatherings for arisan activities, savings and loan cooperatives, training on environmental hygiene and greening, waste banks and other incidental activities. Counseling on Handling of Fishery Products with the theme